PERGESERAN PARADIGMA PENANGGUNGJAWAB NAFKAH KELUARGA:ANALISIS UU PERKAWINAN DAN GENDER - Mustakim, Ahmad; Huda, Afiful (JAS MERAH: Jurnal Hukum dan Ahwal al-Syakhsiyyah, 2023)
This research responds to the changing societal paradigms regarding family financial responsibility, which traditionally were assigned solely to husbands, as stipulated in Islamic law and marriage regulations. However, the globalization era, marked by intense competition, has shifted individuals' roles away from femininity norms that predominantly consider gender factors, towards competitiveness and skills. Women, as wives, also contribute to supporting their husbands' responsibility for providing family financial support. Wives are not limited to being homemakers addressing household issues but also participate in the public sphere as contributors to family financial sustenance. The research aims to examine this societal paradigm shift through the analysis of Marriage Law and gender perspectives, exploring how Marriage Law and gender views respond to the evolving paradigm of financial responsibility, no longer exclusive to husbands but also shared with wives. The findings indicate that the financial responsibility remains primarily placed on the head of the household, i.e., the husband. However, Islamic law and Marriage Law do not prohibit wives from assisting in earning a livelihood for their families. In fact, Islamic law permits wives to contribute to family financial support. Nevertheless, the natural role of a homemaker mandates that a wife must still care for and nurture her children and fulfill her duties towards her husband, even if she actively contributes to supporting the family financially. From a gender perspective, there is no issue with women assisting in family financial matters or engaging in public activities, as long as they do not neglect their primary responsibilities as husbands and wives. The concept of gender emphasizes equality in roles and responsibilities between husbands and wives, both in the public and domestic spheres.